Legal Reform for Investor Protection in Indonesian Crypto Markets: A Comparative Analysis With The MiCA Framework - Rahman, Yogi Muhammad; Jastisia, Mentari; Barora, Siti; Mega Jaya, Belardo Prasetya; Anditya, Ariesta Wibisono (Sekolah Tinggi Hukum Bandung, 2024)
This article examines the urgency of legal reform to enhance investor protection in Indonesia’s crypto asset market, emphasizing the regulatory uncertainty that obscures legal liability in cases of system failure, unilateral platform closure, or investor losses. This research adopts descriptive research specifications, using normative juridical research, using two methods of statutory and comparative approaches. Data collection is done through literature review and then analyzed through qualitative method. The findings reveal that Indonesia’s legal system still relies heavily on individual civil claims based on Article 1365 of the Civil Code, without anticipatory legal instruments. Drawing from MiCA’s best practices, this article highlights the need for prescriptive, risk-based, and investor-oriented legal principles to build a fair and legally certain digital ecosystem.